1997
DOI: 10.1111/j.1365-246x.1997.tb00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Neogene magnetic polarity stratigraphy of some fluviatile Siwalik sections, Nepal

Abstract: S U M M A R YThe magnetostratigraphy of five new sections through the Neogene Siwalik Group of Nepal is presented. Rock magnetic experiments and detailed thermal demagnetization experiments prove that haematite is the carrier of a primary DRM br a PDRM. After stepwise thermal demagnetization of specimens from all sections, directions of characteristic remanent magnetization were obtained. The results show a positive reversal test and exhibit inclination errors of about 20". Due to gaps in exposures and extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 17 publications
3
45
0
1
Order By: Relevance
“…With welldefined normal (D/I: about 0/20) or reverse polarity (D/I: about 180/ -20) after bedding tilt-correction, it passes the reversal test and records inclination shallowing such that the ratio of the tangents of inclinations of the recorded ChRM and the expected field equals to about 0.45. Similar inclination errors are recorded by detrital remanence in sandstones sampled from the present-day riverbeds (Rösler et al, 1997).…”
Section: Magnetization Properties Of Siwalik Sediments In Nepal: a Susupporting
confidence: 78%
See 3 more Smart Citations
“…With welldefined normal (D/I: about 0/20) or reverse polarity (D/I: about 180/ -20) after bedding tilt-correction, it passes the reversal test and records inclination shallowing such that the ratio of the tangents of inclinations of the recorded ChRM and the expected field equals to about 0.45. Similar inclination errors are recorded by detrital remanence in sandstones sampled from the present-day riverbeds (Rösler et al, 1997).…”
Section: Magnetization Properties Of Siwalik Sediments In Nepal: a Susupporting
confidence: 78%
“…For the sake of uniformity, even the Surai Khola section was labelled in this fashion in Rösler et al (1997). Because of diachronous nature of even the identical lithostratigraphic boundaries found in different sections, proliferation of nomenclature has little meaning in chronological sense.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last two decades, it has been demonstrated that the chronology of the Mio-Pliocene fluvial sediments of the Siwalik Group from Pakistan, India and Nepal can be deciphered through correlation of magnetic polarity reversal patterns to the geomagnetic polarity time scale (GPTS) (Barndt et al, 1978;Opdyke et al, 1979;Tauxe and Opdyke, 1982;Johnson et al, 1982Johnson et al, , 1983Tokuoka et al, 1986;Ranga Rao et al, 1988;Opdyke, 1990;Appel et al, 1991;Harrison et al, 1993;Gautam and Appel, 1994;Burbank et al, 1996;Rösler et al, 1997). These data are invaluable for regional chronological correlation throughout the Sub-Himalayan belt.…”
Section: Introductionmentioning
confidence: 96%